Prismatic, basal, and slip strengths of commercially pure Zr by micro-cantilever tests - Wilkinson, A (University of Oxford, 2015)
This study aimed to measure the critical resolved shear strength (CRSS) of individual slip systems in a polycrystalline, commercially pure zirconium sample. The slip strengths of basal ⟨a⟩, prism ⟨a⟩, and pyramidal ⟨c+a⟩ systems in zirconium were determined using micro-cantilever testing. Single-crystal cantilevers ranging from 0.5 µm to 10 µm wide, oriented for single slip, were prepared using focused ion beam (FIB) machining and deflected using a nanoindenter. The critical resolved shear stress (τ_crss) was determined by fitting a crystal plasticity finite element model to the experimental load-displacement data from these micro-bending tests. All three slip systems in alpha-Zr exhibit a marked size effect in bending, described by the relationship CRSS(W) = τ₀ + AWⁿ, where W is the cantilever width, τ₀ is the CRSS at the macroscale, and n = -1. The exponent of approximately -1 aligns with hardening caused by the back stress generated by dislocations piling up at a diffuse barrier, resulting from stress reduction near the neutral axis. The macroscale CRSS values were successfully used to simulate deformation in a conventional macroscopic compression test.